UJI AKTIVITAS ANTIBAKTERI EKSTRAK CATHECHIN TEH PUTIH TERHADAP STREPTOCOCCUS SANGUINIS - Muhamad Zakki (Odonto : Dental Journal, 2017)
Background: Streptococcus sanguinis is known as an early agent of formation of bacterial plaque. White tea is one of plant with various biological activities that are beneficial to human health.Objective: to examine the antibacterial activity of white tea cathechin extract against bacteria S. sanguinis.Methods: test material was white tea cathechin extract. In vitro tests were conducted to obtain minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC).Result: The MIC of White tea cathechin extract was 500ppm (0,5 mg/ml) and MBC was 2000ppm (2mg/ml).Conclusion: White tea cathechin extract has antibacterial properties. White tea cathechin extract can be used as herbal moutwash to control dental plaque.